Processing and Mechanical Properties of Aluminium-Silicon Carbide Metal Matrix Composites - Nuruzzaman, D. M.; Kamaruzaman, F. F. B. (IOP Publishing Ltd., UK, 2016)
In this study, aluminium-silicon carbide (Al-SiC) metal matrix composites (MMCs) of different compositions were prepared under different compaction loads. Three different types Al-SiC composite specimens having 10%, 20% and 30% volume fractions of silicon carbide were fabricated using conventional powder metallurgy (PM) route. The specimens of different compositions were prepared under different compaction loads 10 ton and 15 ton. The effect of volume fraction of SiC particulates and compaction load on the properties of Al/SiC composites were investigated. The obtained results show that density and hardness of the composites are greatly influenced by volume fraction of silicon carbide particulates. Results also show that density, hardness and microstructure of Al-SiC composites are significantly influenced depending on the compaction load. The increase in the volume fraction of SiC enhances the density and hardness of the Al/SiC composites. For 15 ton compaction load, the composites show increased density and hardness as well as improved microstructure than the composites prepared under 10 ton compaction load. Furthermore, optical micrographs reveal that SiC particulates are uniformly distributed in the Al matrix.